2021
DOI: 10.21037/atm-21-1815
|View full text |Cite
|
Sign up to set email alerts
|

Moderately differentiated esophageal squamous cell carcinoma has a poor prognosis after neoadjuvant chemoradiotherapy

Abstract: Background: Neoadjuvant chemoradiotherapy (NCRT) plus surgery is the standard treatment for esophageal squamous cell carcinoma (ESCC); however, further analysis is needed to detail the histopathological characteristics of ESCC and their clinical significance after NCRT. This study aimed to present the pathological characteristics of ESCC and their association with prognosis after NCRT.Methods: All patients with ESCC who underwent NCRT followed by surgical resection at Sichuan Cancer Hospital (China) from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…Based on the latest AJCC staging system (the 8th edition), pathological grade is not a staging factor for patients receiving neoadjuvant therapy. However, we found that the pathological grade was an independent risk factor for OS among patients receiving nCRT plus surgery, which was consistent with that of other reports ( 9 , 10 ). He et al noted that EC patients with poorly differentiated tumors respond better to nCRT than those with well-differentiated or moderately differentiated tumors; however, they have extremely poor long-term survival rates ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the latest AJCC staging system (the 8th edition), pathological grade is not a staging factor for patients receiving neoadjuvant therapy. However, we found that the pathological grade was an independent risk factor for OS among patients receiving nCRT plus surgery, which was consistent with that of other reports ( 9 , 10 ). He et al noted that EC patients with poorly differentiated tumors respond better to nCRT than those with well-differentiated or moderately differentiated tumors; however, they have extremely poor long-term survival rates ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that the pathological grade was an independent risk factor for OS among patients receiving nCRT plus surgery, which was consistent with that of other reports ( 9 , 10 ). He et al noted that EC patients with poorly differentiated tumors respond better to nCRT than those with well-differentiated or moderately differentiated tumors; however, they have extremely poor long-term survival rates ( 10 ). One possible reason is that due to the high turnover, poorly differentiated tumors have a higher probability of being affected by DNA damage and apoptosis following nCRT, which contributes to a higher pathological response ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The oral cancer varies widely with respect to different geographic areas, due to differences in lifestyles, culture and developmental status. 14 Out of the 145,000 deaths reported due to oral cancer, about 77% were reported from less developed countries. 15 Approximately 30,000 new oral cancer cases are identified annually and most of them are in critical stage III or IV.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma 2 assessment of clinico-demographic, histopathological staging and radiological evaluations are considered paramount for timely diagnosis of oral carcinomas. [11][12][13][14][15] MATERIAL & METHODS Current one year (July 2019 to June 2020) crosssectional descriptive study following convenient sampling approach was conducted at Out Patient Department (OPD), Combined Military Hospital Kharian, Gujrat Pakistan. Patients from both genders presenting oral squamous cell carcinoma, above 20-year of age, and willing to participate in the study were included in the study.…”
Section: Introductionmentioning
confidence: 99%